Influence of air dust on anatomo-morphological and biochemical parameters of Plantago Major L - V. Pushkina, Klara; V. Andreeva, Ekaterina; V. Emelianova, Margarita; I. Trukova, Alena; N. Petrova, Viktoria (Edelweiss Applied Science and Technology, 2024)
Pollution has a great impact on the environment. Plants being the representatives of autotrophic organisms are the first to face it. The photosynthesis suppression, water exchange violation, transpiration reduction, growth general oppression and plants’ development are exposed to pollutants. This causes changes in leaf coloration, necroses, premature leaf fall, changes in growth form. The effect of air dust on anatomo-morphological parameters of plantain and the effect of dust pollution on plantain’s (Plantago major L.) production processes have been studied, the dust-holding capacity of plantain leaves has been estimated. The correlation between the dust pollution level and the stomata density in the leaves’ epidermis of model species has been found out. Mass of aboveground organs (g) and leaf lamina area (cm2), the number of stomata on the leaf surface (pcs./mm2), the dust accumulation level on the leaf surface (g) have been analyzed in model species. Weighing was carried out with an accuracy of 0.001 g on electronic scales. According to the performed analysis, we have come to the conclusions: species of the plantain have 10 to 50 mg of dust particles deposited on the leaf surface, the size of leaf plates and the mass of plantain's terrestrial organs decrease as the level of air pollution increases. It should be underlined that air pollution causes an increase in the density of stomata in plantain associated with a reduction in the area of the assimilating apparatus and it can be viewed as one of the compensatory mechanisms.